Coming Clean : Information Disclosure and Environmental Performance - Kraft, Michael E. (Book collections on Project MUSE., 2011)
The authors find that TRI - probably the best-known example of information disclosure - has had a substantial effect over time on the environmental performance of industry. But, drawing on case studies from across the nation, they show that the improvement is not uniform: some facilities have been leaders while others have been laggards. The authors argue that information disclosure has an important role to play in environmental policy--but only as part of an integrated set of policy tools that includes conventional regulation."--Pub. desc